2022
DOI: 10.1177/09697330211072365
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between nurses’ cultural competence and observance of ethical codes

Abstract: Background Cultural competence is considered as one of the main skills of nurses enabling them to provide nursing care for those with different cultures. One of the cases related to nurses’ cultural competence is observance of ethical codes, but it has not been investigated sufficiently in studies. Aim This study has been conducted to determine the relationship between nurses’ cultural competence and observance of ethical codes in practice. Research design This descriptive-correlational study was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…In common with some studies, the results of this study show that nurses can improve ethical compliance through self-improvement, reflection and warning themselves with past mistakes. 41 Interestingly, participants indicated that if the patient's interests were compromised due to themselves or others in the healthcare team, they would not act strictly in accordance with professional ethics in order to protect themselves and their team, but they would try to compensate in other ways, such as offering to comfort the patient, being more tolerant of the patient and providing more discreet professional services. In this way, they gain a psychological balance and do not develop a negative attitude toward observing professional ethics in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In common with some studies, the results of this study show that nurses can improve ethical compliance through self-improvement, reflection and warning themselves with past mistakes. 41 Interestingly, participants indicated that if the patient's interests were compromised due to themselves or others in the healthcare team, they would not act strictly in accordance with professional ethics in order to protect themselves and their team, but they would try to compensate in other ways, such as offering to comfort the patient, being more tolerant of the patient and providing more discreet professional services. In this way, they gain a psychological balance and do not develop a negative attitude toward observing professional ethics in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Discovering the cultural norms, values, beliefs, and practices of the patients being cared for helps in ensuring that they are provided with care that is tailored to their cultural needs 8,33 …”
Section: Developing Cultural Competencementioning
confidence: 99%
“…This can be accomplished by developing self-awareness about cultural differences and how it can promote care provided. 33 Skill Abilities include the capability to cultivate a self-awareness of the cultures present in one's workplace and care setting, as well as the participation in the collection of patient data during admission, with the goal of educating oneself on the cultural values of patients and ensuring that those values are consistently promoted. 35,36 Encounter To be practically involved with patients in the things that correspond to their culture by picking an interest as interaction improves confidence, knowledge, and skills.…”
Section: Characteristics Of Those Who Are Culturally Competent Awarenessmentioning
confidence: 99%
See 2 more Smart Citations